Irritable Bowel Syndrome: Is an Effective Solution Still Elusive? Sindrom razdražljivega črevesja: ali je učinkovita rešitev še vedno tako nedosegljiva? - Globočnik, Ana; Ocepek, Andreja (Acta Medico-Biotechnica, 2025)
Irritable bowel syndrome (IBS) is classified as a disorder of the gutbrain interaction. IBS presents an ongoing challenge for patients and healthcare professionals due to the complexity of the underlying pathophysiology. It is important to approach the patient with IBS in a stepwise manner, beginning with the exclusion of alarming symptoms and other conditions, such as inflammatory bowel disease, colorectal cancer, celiac disease, diverticulitis, carbohydrate malabsorption or maldigestion, chronic pancreatitis, neuroendocrine tumours, hyperthyroidism, small intestinal bacterial overgrowth, bile acid malabsorption or idiopathic bile acid diarrhoea, and gastrointestinal infections, which often have more straightforward or effective treatment. When the diagnosis of IBS is established, the focus is on therapy aimed at alleviating symptoms, such as pain, bloating, and altered bowel habits. Management of IBS includes a strong patient-physician relationship, lifestyle modifications (physical activity and dietary changes), analysing the gut microbiota, using probiotics, pharmacologic therapy, and psychological support, including psychotherapy and stress modulation.